Self-Control Therapy on the Dietary Behavior of Adolescents with Type 1 Diabetes Mellitus - Nanik; Salim, Lydia Corazon; Setiono, Vivi (Faculty of Psychology, Universitas Surabaya, 2009)
Adolescents with Type 1 Diabetes Mellitus (DM-1) usually show a lack of responsibility to maintain their healthy lifestyle, especially the obedience in controlling their dietary behavior. The main factor of this disobedience is lack of self control and self-endurance. This research was aimed to see the impact of self-control therapy on dietary behavior The applied self control ther- apy was the reformative type to alter the lifestyle, the behavior patterns, and the destructive ha- bits directly. Participants were two adolescents with DM-1, aged 15 and 22 years old participants, who were obtained through a snowball sampling technique. The questionnaire, which was based on the self control and the records of the dietary behaviors before, during and after therapy, was used to collect the data. The results showed that the self control therapy has a significant impact in helping the adolescents with DM-1 to alter their behavior towards a better diet. Remaja penyandang Diabetes Mellitus Tipe 1 (DM 1) umumnya menunjukkan kurang bertanggung jawab mengupayakan gaya hidup sehat, terutama kepatuhan dalam mengendalikan perilaku makannya. Faktor utama ketakpatuhan ini adalah kurangnya kendali diri dan ketahanan diri. Penelitian ini bertujuan melihat dampak terapi kendali diri terhadap perilaku makan. Terapi kendali diri terpakai adalah jenis reformatif untuk mengubah gaya hidup, pola perilaku, dan kebiasaan buruk secara langsung. Para peserta adalah dua orang remaja penyandang DM 1, berusia 15 dan 22 tahun yang diperoleh memakai teknik sampling bola salju. Peserta penelitian ini diperoleh memakai teknik snowball. Kuesioner yang didasarkan pada kendali diri dan catatan perilaku makan sebelumnya, terapi selama dan sesudah terapi, dipakai untuk memperoleh data. Hasil-hasil menunjukkan bahwa terapi kendali diri memiliki dampak signifikan dalam membantu remaja penyandang DM 1 untuk mengubah perilaku ke diet yang lebih baik.